RURAL YOUTH LOCAL CHAMPIONS SUPPORT FOR RURAL DEVELOPMENT POLICY AND PROGRAM - Abdul Malek, Jalaluddin; Baharudin, Rabeah Adawiyah; -, Alfitri; Tahir, Zurinah (PLANNING MALAYSIA, 2022)
Rural youth development must be exposed to the genuine intents and goals of the country’s rural development direction in guiding the rural youth. As a result, this study seeks to find Local Champions (LC) support for rural development policies through the Rural Business Champions (RBC) lens. This study uses parallel mixed methods. The findings show that the LC technique and the Rural Development Master Plan should be promoted to the youth who agreed the most. However, all the mean scores are high, and RBC supported all programs to enhance LC among the rural youth. Interviews revealed a need for programs that develop passion and drive among rural youth and an emphasis on implementing entrepreneurial knowledge. Thus, this study found that the local youth participating in local champion policies and programs need to be exposed to knowledge, passion, and mentor by being included in local champions practices.